The role of neuropeptides in pathophysiology of rhinitis - Gawlik, Radosław (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Neuropeptides and neuropeptide-containing nerves are proven to exist in the human nasal mucosa. The presence and distribution of NPY, CGRP, neurokinin A and SP nerve fibres and neuroendocrine cells have been confirmed. Released neuropeptides and kinins are involved in vasodilatation, increased vascular permeability, irritation of neural endings and inflammatory cell migration, causing symptoms of allergic rhinitis. Different studies have demonstrated that neuropeptides have a great potential biological role in inflammatory mechanisms in the nasal mucosa. The role of neuropeptides and kinins in nasal pathophysiology is discussed.